The antimicrobial peptide Temporin L impairs E. coli cell division by interacting with FtsZ and the divisome complex - Di Somma, Angela; Avitabile, Concetta; Cirillo, Arianna; Moretta, Antonio; Merlino, Antonello; Paduano, Luigi; Duilio, Angela; Romanelli, Alessandra (Biochimica et biophysica acta. General subjects, 2020)
The comprehension of the mechanism of action of antimicrobial peptides is fundamental for the design of new antibiotics. Studies performed looking at the interaction of peptides with bacterial cells offer a faithful picture of what really happens in nature. In this work we focused on the interaction of the peptide Temporin L with E. coli cells, using a variety of biochemical and biophysical techniques that include: functional proteomics, docking, optical microscopy, TEM, DLS, SANS, fluorescence. We identified bacterial proteins specifically interacting with the peptides that belong to the divisome machinery; our data suggest that the GTPase FtsZ is the specific peptide target. Docking experiments supported the FtsZ-TL interaction; binding and enzymatic assays using recombinant FtsZ confirmed this hypothesis and revealed a competitive inhibition mechanism. Optical microscopy and TEM measurements demonstrated that, upon incubation with the peptide, bacterial cells are unable to divide forming long necklace-like cell filaments. Dynamic light scattering studies and Small Angle Neutron Scattering experiments performed on treated and untreated bacterial cells, indicated a change at the nanoscale level of the bacterial membrane. The peptide temporin L acts by a non-membrane-lytic mechanism of action, inhibiting the divisome machinery. Identification of targets of antimicrobial peptides is pivotal to the tailored design of new antimicrobials. [Display omitted] •The mechanism of action of TL is investigated by a functional proteomic approach.•The morphology of bacterial cells upon interaction with TL is detected by SANS.•TL inhibits the cell division process, by binding to FtsZ.